2020
DOI: 10.3389/fphar.2020.01039
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the General Medication Adherence Scale in Pakistani Patients With Rheumatoid Arthritis

Abstract: The aim was to validate the Urdu version of General Medication Adherence Scale (GMAS) in patients with rheumatoid arthritis disease. Methods: A 2-month (March-April 2019) cross-sectional study was conducted in randomly selected outpatients with rheumatoid arthritis. The sample size was calculated using item-subject ratio of 1:20. The scale was evaluated for factorial, concrete, concurrent, and known group validities. Concrete validity was established by correlating scores of EQ-5D quality of life scale and GMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 62 publications
2
20
0
Order By: Relevance
“…Previous studies have reported a 3-factor structure of GMAS scale in patients with chronic diseases. We confirmed the 3-factor model and calculated the fit indices ( Naqvi et al, 2018 , Naqvi et al, 2019a , Naqvi et al, 2020 ). The fit indices were in the acceptable range that indicated that the 3-factor model was fit.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Previous studies have reported a 3-factor structure of GMAS scale in patients with chronic diseases. We confirmed the 3-factor model and calculated the fit indices ( Naqvi et al, 2018 , Naqvi et al, 2019a , Naqvi et al, 2020 ). The fit indices were in the acceptable range that indicated that the 3-factor model was fit.…”
Section: Discussionsupporting
confidence: 64%
“…Adult male and female Saudi out-patients above age of 18 years who had a confirmed diagnosis of a chronic disease, with or without co-morbidities, on long-term therapy during implementation phase of adherence, for at least a month before study, were invited to participate in the study. The implementation phase of adherence is the stage in which the patient continues to take medications from the time of the first dose until the last one ( Dowrick et al, 2005 , Vrijens et al, 2012 , Naqvi et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…As expected from relevant studies [ 37 40 ], the results of “known group comparisons” showed that females and patients with insurance had better adherence than male patients and those who lacked insurance.…”
Section: Discussionsupporting
confidence: 67%
“…The method of known groups is a typical method for supporting construct validity and is given when a test can discriminate between a group of people known to have a specific characteristic and a group who do not have the characteristic. The instrument's total score was compared based on gender and insurance coverage [37][38][39][40].…”
Section: Construct Validitymentioning
confidence: 99%
“…Regarding the validation of the GMAS studies (two interviews four weeks apart), this figure was 0.996 (p < 0.01) or 0.861 (p < 0.01). For the validation of the GMAS in osteoarthritis patients (two interviews three weeks apart), this figure was 0.875 (p < 0.001) [12,13,22,23]. In these studies, Spearman's correlation coefficients indicate that the GMAS has good stability; even though the time between the two interviews was different, the GMAS was still at a good correlation.…”
Section: Discussionmentioning
confidence: 89%